Architecture, Religion, and Tuberculosis in Sainte-Agathe-des-Monts, Quebec - Adams, Annmarie; Poutanen, Mary (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2009)
AbstractThis paper explores the architecture of the Mount Sinai Sanatorium in Sainte-Agathe-des-Monts (Qc) to disentangle the role of religion in the treatment of tuberculosis. In particular, we analyze the design of Mount Sinai, the jewel in the crown of Jewish philanthropy in Montreal, in relation to that of the nearby Laurentian Sanatorium. While Mount Sinai offered free treatment to the poor in a stunning, Art Deco building of 1930, the Protestant hospital had by then served paying patients for more than two decades in a purposefully home-like, Tudor-revival setting. Using architectural historian Bernard Herman's concept of embedded landscapes, we show how the two hospitals differed in terms of their relationship to site, access, and, most importantly, to city, knowledge, and community. Architects Scopes & Feustmann, who designed the Laurentian hospital, operated an office at Saranac Lake, New York, America's premier destination for consumptives. The qualifications of Mount Sinai architects Spence & Goodman, however, derived from their experience with Jewish institutions in Montreal. Following Herman's approach to architecture through movement and context, how did notions of medical therapy and Judaism intersect in the plans of Mount Sinai?